Oei Tjeng Hien dan Masjid Lautze: Politik Identitas Tionghoa Muslim - Raymon, Alexander; Wijayati, Putri Agus (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Chinese Muslims face the issue of cultural identity as a double minority. In an existential context, this group is a minority within their ethnic religion, and remains a minority among other ethnicities in Indonesia. This study uses qualitative and quantitative methods to discuss Chinese Muslim politics as an expression of their faith identity in building brotherhood with Muslims in Indonesia while maintaining their cultural identity as ethnic Chinese to avoid alienation within their community. Through this study, it was found that the socio-political life of Chinese Muslims in Jakarta in general, and at the Lautze Mosque in Jakarta in particular, is a manifestation of metropolitan Islam combined with an inclusive Chinese identity. The political vision of Chinese Muslims, expressed by maintaining their cultural background, is also demonstrated through the political movement of Oei Tjeng Hien, which is based on universal Islamic teachings that emphasize human values.